Determining Level of Knowledge of the State Language of Georgia for Civil Servants and People Seeking Georgian Citizenship - Odzeli, Marika (Actual Problems of Kartvelology, 2013)
For the unification of teaching, learning and assessment of contemporary languages within the European space, common European language policy is based on specific system of language knowledge, which has been developed and refined for years in the Council of Europe. This is a six-level system of language that is learneroriented and meets the requirements and needs of learners of any age. Reference Level Description for languages is defined in accordance with the analysis of linguistic categories, functions, grammar and vocabulary. Linguistic skills comprise reception (listening, reading) and production (speaking, writing). According to the common European requirements, we have worked out the Reference Level Description for the Georgian as a foreign language. This was a pilot version which has been efficiently used and has undergone several changes for years. This RLD was discussed on trainings, seminars and workshops. It was eventually refined and established as the most appropriate version at the Georgian Language Division, Ministry of Education and Science of Georgia. This very version is presented in the article. We would like to state the following: requirements of contemporary life conditioned the need to determine the level of knowledge of the state language for the civil servants and people seeking Georgian citizenship. As we have mentioned above, we have worked out the Reference Level Description for the Georgian as a foreign language which will enable us to determine the level of the language knowledge of people seeking Georgian citizenship. Besides, we regard that a competent committee should be founded which will determine the level of knowledge of the people seeking Georgian citizenship. As far as civil servants are concerned, we need to think whether the description created by us is appropriate to determine the level of knowledge of civil servants. This kind of description can be prepared for Georgian as a native language and on its basis, the level of knowledge of civil servants can be defined.